Human Rights, Economic Rights, Socio-Cultural Rights: A Critical Analysis of Law No. 4/2012 on Employment in Timor Leste - Domingos Franklin Soares; Edgar Antonio F.R. Da Costa; Agostinho de Jesus Madeira; Cevanio Leo Ribeiro; Lourenca Cardoso da Costa; Antonio Soares ribeiro (CV. Ulil Albab Corp, 2025)
This study aims to determine Human Rights, Economic Rights, Socio-Cultural Rights: Critical Analysis of Law No. 4 of 2012 concerning Manpower in Timor Leste. The results of this study indicate that Through an inclusive and strategic approach and through Law No. 4/2012 can be an effective instrument to advance human rights, social justice and economic development in Timor-Leste.